Heavy metals in mangrove sediments along the Selangor River, Malaysia - Nyangon, Laurna; Zainal, Ahmad Nur Syahmi; Mohamad Pazi, Ahmad Mustapha; Gandaseca, Seca (Universitas Hasanuddin, 2019)
Mangroves are woody plants that grow at the interface between land and sea in tropical and subtropical latitudes where they exist in conditions of high salinity, extreme tides, strong winds, high temperature, and muddy anaerobic soils. The objectives of this study were to determine the selected heavy metals Copper (Cu), Zinc (Zn) and Lead (Pb) contamination in mangrove sediments at the Selangor River, Kampung Kuantan, Kuala Selangor, Selangor, Malaysia; and to compare heavy metals content in mangrove sediments between different plots and different sediment depths. Physical properties (sediment texture and sediment moisture) and chemical properties (pH water, electrical conductivity, and selected heavy metals) of sediments were determined by different plots and depths. The element of Pb was analyzed using the Inductively Coupled Plasma (ICP), whereas Cu and Zn using the Atomic Absorption Spectrometer (AAS). Data obtained were analyzed using the Statistical Analysis System (SAS) version 9.4 software. The results showed that the sediment texture was in the class of sandy clay, and soil moisture in all plots and at all depths were high. The contamination of sediment is affected by many factors, including soil pH and soil electrical conductivity. Cu, Zn and PB in sediment were determined around 1.00-10.60 mg/kg, 215.40-259.00 mg/kg and 18.83-28.59 mg/kg respectively, and were found to experience a significant difference between the plots, but not a significant difference between depths. The sediment in all plots and at all depths was contaminated with these heavy metals because of it being surrounded by residential and industrial areas, combined with particular recreational activities, agriculture and fishing along the Selangor River.